Improved Direct Torque Control of Induction Motor for Torque Ripple Minimization - Tomas Esparza Sola; Huang Jen Chiu; Yu-Chen Liu; Arief Noor Rahman (IEEE Access, 2022)
A new direct torque control (DTC) method of an induction motor (IM) which minimizes torque ripple $\left ({T_{ripp} }\right)$ while preserving all the conventional DTC advantages is presented in this paper. Large $T_{ripp}$ and current ripple are the main drawbacks of the conventional DTC. To address this problem, this paper gives a qualitative analysis of the main $T_{ripp}$ sources of the conventional DTC. A novel strategy to reduce $T_{ripp}$ in the constant $T$ and in the field weakening (FW) regions is proposed. The performance of the proposed method is evaluated and compared with a recently published method that aims for the same goals that are pursued in this paper, as well as with the conventional DTC. The analysis has been carried out on the basis of the results obtained by theoretical analysis and hardware implementation.